Enseñanza del español y contexto social. La familia como recurso temático para la clase de conversación destinada a estudiantes surcoreanos / Spanish teaching and social environment. The family as a speaking topic for conversation classes in South Korea - Jorge Manuel Mendoza Puertas (Tejuelo: Didáctica de la Lengua y la Literatura)
In great part, the success or failure of a thematic resource in a conversation class of a foreign language depends on the social environment and educational context of students. In this paper, after we carry out an approach not only to some aspects of Korean society, but to Korean college student profile, we consider that the topic of new family models is a productive thematic resource for a speaking class of Spanish, and we propose a brief didactic guidance to work with.